Work motivation system - Vovk, Taras; Vlasenko, Ludmila (My University, 2014)
At the present stage of economy development, one of the main tasks of the managers is to motivate their employees to work effectively to organize qualitative and effective activity, aimed to achieve the goals of the company. Employees should understand that achieving the objectives of the company, they will reach their personal goals with the help of the benefits that the company is offering for them.
Keywords: development; economy; motivation work; розвиток; економіка; мотивація роботи; развитие; экономика; мотивация работы; кафедра ділової іноземної мови та міжнародної комунікації